Who says what to whom? Alignments and arguments in EU policy-making. Issue 5 (3rd September 2017) - Eising, Rainer; Rasch, Daniel; Rozbicka, Patrycja; Fink-Hafner, Danica; Hafner-Fink, Mitja; Novak, Meta
Abstract: In the EU multilevel polity, domestic interest groups seek to shape EU legislation by accessing both national and EU institutions. Previous studies indicated that institutional and issue contexts as well as organisational characteristics shape their strategies of interest representation. However, we know much less about how alignments and arguments impact on their participation in EU and national policy consultations. Addressing this gap, we investigate the lobbying strategies of almost 2900 national interest organisations from five member states (Germany, the Netherlands, Slovenia, Sweden, and the United Kingdom) on 20 EU directive proposals also bringing a new empirical scope to the study of multilevel interest representation. The findings indicate that alignments and arguments shape the participation of domestic interest groups in consultations on EU policies. We infer from our study that some general predictions of interest group behaviour are overstretched and outline four major variations of interest representation routines.